Analysis of Factors Related to the Incidence of Ventilator-Associated Pneumonia (VAP) in the Intensive Care Unit - Yudi Jaya Cahyana; Irfansyah Baharuddin Pakki; Ida Ayu Indira Dwika Lestari; Ratno Adrianto; Yadi Yadi; Akhmad Azmiardi (Indonesian Journal of Global Health Research, 2025)
Ventilator-associated pneumonia (VAP) occurs in patients who have been on mechanical ventilation with an endotracheal tube (ETT) for at least 48 hours. This type of pneumonia typically arises as a result of nosocomial infections or Healthcare-Associated Infections (HAIs) and is commonly linked to the use of ventilators in hospital settings. This study was to identify the factors associated with the incidence of VAP among patients admitted to the Intensive Care Unit of Abdoel Wahab Sjahranie Hospital, Samarinda. Method: A cross-sectional study was conducted. The study population consisted of all patients who had undergone mechanical ventilation in the ICU without a prior history of pneumonia, totaling 118 respondents, using the HAIs bundle observation tool and direct observation. Chi-square and multiple logistic regression were used for statistical analysis, along with a predictive model. The results showed that the prevalence of VAP among respondents in the ICU was 5.9%. Factors significantly associated with the incidence of VAP included duration of ventilator use (p = 0.000), oral hygiene procedures (p = 0.000), head-of-bed elevation to 30–45° (p = 0.007), hand hygiene compliance (p = 0.015), and aseptic suctioning procedures (p = 0.043). The multivariate analysis identified duration of ventilator use ≥96 hours as the most dominant factor, with the highest Odds Ratio (OR = 13.975; 95% CI: 0.753–227.435). Duration of ventilator use was the most significant factor associated with an increased risk of VAP, with patients ventilated for ≥96 hours being 13 times more likely to develop VAP compared to those ventilated for <96 hours. Proper oral hygiene, appropriate head-of-bed elevation (30–45°), compliance with hand hygiene, and aseptic suctioning procedures were also found to be significantly associated with VAP incidence among ICU patients at Abdoel Wahab Sjahranie Hospital